Analysis of the Mechanism of Maslinic Acid on Papillary Thyroid Carcinoma Based on RNA-Seq Technology. (7th September 2022) - Li, Rong; Zhang, Yanjiao; Xiang, Runqing; Lin, Aihe; Xia, Zongxiao; Long, Xiaomei; Guo, Shuang; Fan, Yuan; Chen, Zukun
Abstract : Objective. This study analyzed gene sequence changes in the thyroid papillary carcinoma (PTC) cell line TPC-1 treated with the natural compound maslinic acid (MA) through RNA-sequencing (RNA-seq) and identified the necessary genes to provide a basis for the study of the molecular mechanism of action of MA in PTC treatment. Methods. RNA-seq technology was used to detect genetic differences between the normal cell group (Nthy-ori 3-1) and the TPC-1 cell group (N vs T). Then, gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, Venn diagram analysis of shared genes, and protein–protein interaction (PPI) network analysis were used to analyze the therapeutic effect of the MA on TPC-1 cells. Real-time quantitative PCR (qRT-PCR) was used to verify six key genes. Results. GO and KEGG analyses showed that four crucial signaling pathways are related to TPC development: cytoplasmic molecule (cell adhesion molecules), neuroactive ligand–receptor interaction, tumor transcriptional disorder, and cytokine–cytokine interaction. The Venn diagram revealed 434 genes were shared between the MA vs T-group and 387 genes were shared between the MATH vs T and N vs T groups. PPI and ClueGO showed that NLRP3, SERPINE1, CD74, EDN1, HMOX1, and CXCL1 genes were significantly associated with PTC, while CXCL1, HMOX1, and other factors were mainly involved in the cytokine–cytokine interaction. The qRT-PCR results showed that the expression of NLRP3, EDN1, HMOX1, and CXCL1 genes was significantly upregulated in the TPC-1 group but significantly downregulated after MA treatment (p < 0.01 ). SERPINE1 and CD74 genes were not expressed in TPC-1 cells, whereas they were significantly upregulated after MA treatment (p < 0.01 ). Conclusions. This present study proves for the first time that MA can treat PTC, and the preliminary identification of key genes and rich signal transduction pathways provides potential biomarkers. It also provides potential biomarkers for the treatment of PTC with the natural compound MA and preliminarily discusses the therapeutic mechanism of action of MA against PTC, which is helpful for the further diagnosis and treatment of PTC patients.